(untitled) - Packer, James Innell; (1926-2020) (Great Britain, 1992)
This book is a look at how to be holy and pleasing to God amid all the pressures of present day. JI Parker brings us back to where God wants us to be. He shows us that holiness is nothing less than a lifelong passion for loving God and following His ways.
Keywords: Christianity -- Religious life